For love of Ivy [videorecording (DVD)] - Mann, Daniel, 1912-1991; Poitier, Sidney; Lincoln, Abbey; Bridges, Beau (Kino Lorber, 2018)
A gambler is persuaded to be the boyfriend of a young maid who wants to quit and go to secretarial school.